Design and Fabrication of Dry Chili Seed Extraction Machine - Ibrahim, Mohd Norihan; Mohamed Zalami, Muhammad Naqiuddin (Research Progress in Mechanical and Manufacturing Engineering, 2021)
The application of automatics device or machine in the preparation of food based product in the household or small or medium scale food industries is truly essential. Among the frequent works done by housewife or chefs at the restaurant is cutting the dried chilies in preparing the appropriate menu’s or dishes for lunch, dinner or for food business purposes. An idea of creating and developing suitable device or machine to facilitate the process of cutting chilies has come through and therefore a prototype named Dry Chili Seed Extraction Machine was built and created. The machine is used by housewives or chefs whom normally need to prepare food for their family and customers. The main purpose of this dries chilies seed separator machine is to save the time used to separate the seeds from the chili. Using existing methods, it may take longer time to prepare it and can cause irritation to the skin. Based on the existing method or technique used to separate the seeds, this device also able to cut the chilies into several pieces. With customization and improvement to the device, it is capable to solve the problem of difficulty to separate the seed with different size of chili. As the capability of the machine is increase, the more quality of the product can be produced. This project will help housewives or chef to save more time and prevent injury.